On the theory of hypersurfaces in some B-spaces of hyperbolic type - Kriščiūnaitė, A. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Л. Крищюнайте. К теории гиперповерхностей некоторых В-пространств гиперболического типа A. Kriščiūnaitė. Kai kurių hiperbolinio tipo B-erdvių hiperpaviršių teorijos klausimu